Relation between systemic inflammatory markers, peripheral muscle mass, and strength in limb muscles in stable COPD patients - Ferrari, Renata; Caram, Laura M. O.; Faganello, Marcia M. [UNESP]; Sanchez, Fernanda F.; Tanni, Suzana E.; Godoy, Irma (Dove Medical Press Ltd, 2015)
The aim of this study was to investigate the association between systemic inflammatory mediators and peripheral muscle mass and strength in COPD patients. Fifty-five patients (69% male; age: 64 +/- 9 years) with mild/very severe COPD (defined as forced expiratory volume in the first second [FEV1]=54%+/- 23%) were evaluated. We evaluated serum concentrations of IL-8, CRP, and TNF-alpha. Peripheral muscle mass was evaluated by computerized tomography (CT); midthigh cross-sectional muscle area (MTCSA) and midarm cross-sectional muscle area (MACSA) were obtained. Quadriceps, triceps, and biceps strength were assessed through the determination of the one-repetition maximum. The multiple regression results, adjusted for age, sex, and FEV1%, showed positive significant association between MTCSA and leg extension (0.35 [0.16, 0.55]; P=0.001), between MACSA and triceps pulley (0.45 [0.31, 0.58]; P=0.001), and between MACSA and biceps curl (0.34 [0.22, 0.47]; P=0.001). Plasma TNF-alpha was negatively associated with leg extension (-3.09 [-5.99, -0.18]; P=0.04) and triceps pulley (-1.31 [-2.35, -0.28]; P=0.01), while plasma CRP presented negative association with biceps curl (-0.06 [-0.11, -0.01]; P=0.02). Our results showed negative association between peripheral muscle mass (evaluated by CT) and muscle strength and that systemic inflammation has a negative influence in the strength of specific groups of muscles in individuals with stable COPD. This is the first study showing association between systemic inflammatory markers and strength in upper limb muscles.
Keywords: Inflammation; skeletal muscle; X-Ray Computed Tomography